0153 Thiel Is Real – But Not Just For Surgeons?. (1st November 2014) - Tomlinson, James; Yiasemidou, Marina; Glassman, Daniel; Gough, Michael; Roberts, David; Miskovic, Danilo
Abstract : Background: Simulation of technical skills and procedures is difficult when training higher surgical trainees and consultants. Part task simulators have a role for developing familiarity but the gold standard is cadaveric surgery. Cadaveric tissue preserved using traditional formaldehyde techniques leaves tissue inelastic and thus only suitable for anatomical demonstration. Fresh frozen tissue provides highly realistic tissue feel and surgical training but at a high cost with limited lifespan. Methodology: Three cadavers were prepared using the Thiel embalming technique for a local pilot study. A multi-specialty interactive workshop was then held. Surgeons attended from a number of specialties: Maxillofacial surgery, plastic surgery, ENT surgery, neurosurgery, orthopaedic surgery, spinal surgery, general surgery, vascular surgery, urology and thoracic surgery. Surgeons were asked to provide structured feedback on the tissue. In addition a number of workshops were held to discuss the potential wider implications and uses of this technique to aid in surgical training. Outcomes: Feedback was almost universally positive with Thiel embalmed tissue having highly realistic feel and handling. Thiel tissue was suitable for surgical procedures both open and laparoscopic, and further work to trial arthroscopic procedures is planned. Work is also to be undertaken to assess the suitability of Thiel cadavers for anaesthetic training on airway management and ventilation. A role for Thiel cadavers for minimal invasive liver biopsy has also been suggested recently. 1 Potential impact: We believe Thiel cadavers have a huge role to play in surgical training due to their highly realistic feel and long lifespan. The key obstacle will be the cost of providing cadaveric tissue. The long lifespan of Thiel cadavers, and also the ability to ventilate would allow highly realistic immersive theatre simulation alongside technical skill and procedural simulation. Through collaboration in this way it may be possible to access this costly but valuable training resource. Reference: Eisma R, Gueorquieva M, Immel E, Toomey R, Mcleod G, Soames R, Melzer A. Liver displacement during ventilation in Thiel embalmed human cadavers - a possible model for research and training in minimally invasive therapies. Minim Invasive Ther Allied Technol . 2013 Sep;(22):291–6